Kelayakan Finansial dan Analisis Nilai Tambah pada Pengolahan Teh Putih di PT. Bali Cahaya Amerta Gianyar Bali - Wiartha, I Dewa Gede Agung Sastra; Wrasiati, Luh Putu; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 2 (2021): Juni, 2021)
White tea are superior products at PT. Bali Cahaya Amerta and still not so many other companies in producing it. The purpose of the study is to , determine the financial feasibility of white tea processing at PT. Bali Cahaya Amerta, determine the added value generated from the processing of white tea at PT. Bali Cahaya Amerta, and determine the feasibility of white tea at PT. Bali Cahaya Amerta if there is an increase in operating costs and a decrease in income using sensitivity analysis. Financial feasibility analysis uses quantitative descriptive analysis using the calculation of profit and loss, Net Present Value, Internal Rate of Return, Net B / C Ratio, Payback Period, and Break Event Point, and value added analysis using the Hayami method . Production of white peon y and silver needles is feasible, with Net Present Value results of   Rp. 4,505,933,033 . Internal Rate of   Return of 5.49% shows that the rate of return is greater than the specified bank interest rate. Payback Period for 2 years 3 months. B/C ratio of 1.55 . White peony added value obtained a value of Rp. 8 60 , 000 per kg, the ratio of added value is 110 . 25%. While the added value of the silver needle is Rp. 4 3 0 , 000 per kg, value added ratio of 4 7 . 77 %. The sensitivity analysis scenario shows that both an increase in operating costs of 1 . 5% -4% and revenue decrease d 1 . 5% -2 . 5% resulting in a positive NVP. So that the business of white peony and silver needle is feasible. Keywords: white tea, financial feasibility, value added